Ideology and Art - Nežnovas, Genadijus (Problemos, 1976)
The article considers some problems of the interrelation between ideology and art. It is shown that the solution of these problems depends on the conceptions of ideology and art. The author believes that the ideological effect of art is indirect. Art imparts emotionality to social evaluations which is easily transmitted to people and regulates their attitude to social phenomena reflected in works of art. On the other hand, scientific ideology aids in correctly reflecting reality which enhances the persuasiveness of art and its lasting effect on man.